The Dichotomy of Memantine Treatment for Ischemic Stroke: Dose-Dependent Protective and Detrimental Effects. Issue 2 (February 2015) - Trotman, Melissa; Vermehren, Philipp; Gibson, Claire L; Fern, Robert
Excitotoxicity is a major contributor to cell death during the acute phase of ischemic stroke but aggressive pharmacological targeting of excitotoxicity has failed clinically. Here we investigated whether pretreatment with low doses of memantine, within the range currently used and well tolerated for the treatment of Alzheimer's disease, produce a protective effect in stroke. A coculture preparation exposed to modeled ischemia showed cell death associated with rapid glutamate rises and cytotoxic Ca 2+ influx. Cell death was significantly enhanced in the presence of high memantine concentrations. However, low memantine concentrations significantly protected neurons and glia via excitotoxic cascade interruption. Mice were systemically administered a range of memantine doses (0.02, 0.2, 2, 10, and 20 mg/kg/day) starting 24 hours before 60 minutes reversible focal cerebral ischemia and continuing for a 48-hour recovery period. Low dose (0.2 mg/kg/day) memantine treatment significantly reduced lesion volume (by 30% to 50%) and improved behavioral outcomes in stroke lesions that had been separated into either small/striatal or large/striatocortical infarcts. However, higher doses of memantine (20 mg/kg/day) significantly increased injury. These results show that clinically established low doses of memantine should be considered for patients 'at risk' of stroke, while higher doses are contraindicated.